Penerapan Modern Farm untuk Menunjang Higienitas dan Kemadirian Pangan di Pondok Pesantren Darul Mutaqin Kota Batu - Teguh Dwi Widodo; Dwi Kristanto; Arief Budi Nugroho; Lilis Yuliati; Redi Bintarto; Rudianto Raharjo (Universitas Muhammadiyah Semarang, 2024)
One of the important contributions from the academic community of Brawijaya University is the empowerment of students in the boarding school setting. A range of empowerment programs have been adopted, encompassing the enhancement of traditional beverage production tools and workshop tools, as well as the introduction of handicraft innovations to augment income. The economy of the students and members of the Darul Mutaqin Islamic boarding school in Dau Village, Batu City, primarily relies on donations, supplemented by revenue generated from the sale of herbal goods. The school is strategically located next to rice fields, which offer ample natural resources. Food self-sufficiency can be achieved by utilizing animal husbandry techniques that involve feeding animals with nutritious green feed derived from agricultural waste, such as water hyacinth and maize stalks. This approach holds significant promise. Presently, the livestock industry at Darul Mutaqin Islamic Boarding School, namely in poultry farming, remains underdeveloped despite the ample availability of natural resources. Poultry farming, a generally manageable approach, might suffer a decrease in economic profitability if not adequately planned. The implementation of suitable technology via the Doktor Mengabdi initiative is anticipated to enhance students' proficiency in animal husbandry, augment livestock yield, and uphold environmental well-being. Darul Mutaqin's future goals include attaining financial self-sufficiency. This effort offers solutions by implementing a cutting-edge pilot project for a contemporary livestock system that integrates diverse mechanization and automation technology. The purpose of these suitable technologies is to generate sustainable poultry products, hence benefiting the pesantren community.